1984
DOI: 10.1016/s0735-1097(84)80055-8
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular performance in septic shock: A combined radionuclide and hemodynamic study

Abstract: Twenty-five patients with septic shock underwent simultaneous radionuclide ventriculography and right heart catheterization to clarify the role of the right ventricle in this syndrome. A depressed right ventricular ejection fraction (less than 38%) was present in 13 patients and was found in patients with elevated cardiac output (4 of 6 patients) and with normal or low cardiac output (9 of 19 patients). Right ventricular dysfunction was seen with or without acute respiratory failure. In eight patients, a depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
11

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(76 citation statements)
references
References 27 publications
4
61
0
11
Order By: Relevance
“…In septic shock, right heart failure can lead to death (Kimchi et al, 1984) and, in pulmonary embolism, most patients who succumb do so within minutes to few hours after onset of symptoms. Therefore drugs that antagonise vasoconstrictive mediators could be effective overall if given in the initial phase of hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%
“…In septic shock, right heart failure can lead to death (Kimchi et al, 1984) and, in pulmonary embolism, most patients who succumb do so within minutes to few hours after onset of symptoms. Therefore drugs that antagonise vasoconstrictive mediators could be effective overall if given in the initial phase of hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%
“…C'est lors de l'augmentation de la postcharge du VD, à l'occasion de la mise sous ventilation mécanique ou lors de la vasoconstriction pulmonaire hypoxique ou du sepsis, que la défaillance systolique du coeur droit se démasque. Cette défaillance survient dans plus de la moitié des cas de sepsis si l'on prend la fraction d'éjection du VD [55,56], mais dans moins de 20 % des cas si l'on prend comme indice de défaillance du VD le ratio des diamètres télédiastoliques du VD sur le VG, supérieur à 0,6 [29]. Un ratio VD/VG > 1 signe une dilatation majeure du VD.…”
Section: Dysfonction Du Vdunclassified
“…Improvement in these physiologic parameters was also reported when epinephrine was used as a first-line agent [10]. Although right ventricular dysfunction is frequently documented in septic shock [2,[11][12][13][14][15][16][17] and could be considered as a prognostic factor [14,18], few studies have reported therapeutic interventions such as fluid loading [13,17] or the use of catecholamines [18,19], and no study has investigated the effects of or the possible advantage of epinephrine on right ventricular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The main hemodynamic disturbances of septic shock include decreased systemic vascular resistance, hypovolemia, tachycardia, and elevated cardiac output after volume loading, despite left [1] and right [2] ventricular dysfunction. In addition to appropriate antimicrobial therapy and surgery as needed, the treatment of septic shock is based on volume expansion and infusion of catecholamines such as dopamine, dobutamine [3][4][5], and norepinephrine [6].…”
Section: Introductionmentioning
confidence: 99%